STRATEGI PENINGKATAN MUTU KEAMANAN PRODUK BAKERI INDUSTRI KECIL MENENGAH MELALUI PENERAPAN GOOD MANUFACTURING PRACTICES (GMP) = THE STRATEGY OF IMPROVING FOOD SAFETY BASE ON IMPLEMENTATION GOOD MANUFACTURING PRACTICES (GMP’S) ON SMALL-MEDIUM ENTERPRISES BAKERY - Himawan Adinegoro (Majalah Ilmiah Pengkajian Industri, 2016)
AbstractThe objective of this research is to formulate strategy of improving food safety base on implementation Good manufacturing Practices (GMP’s). This paper presents a Swot analysis regarding the implementation of GMP’s on smallmedium enterprises bakery in Bogor. SWOT is an expert choice justification model which is used to engineer the structural analysis model by taking several elements of the strategic environmental factors. SWOT analysis for the strategic environmental factors has identified the significant aspect of the supporting elements, constraints and, the groups of the alternative strategy. Interpretative Structural Modelling (ISM) is used to find out the principal sub-elements of each strategy and stakeholders elements have been analysed to enrich the formulate strategy. Complete analysis of this research has built alternative formulation strategy for region superiority improving food safety base on implementation GMP’s, with considering respective limitation. Abstrakproduk bakeri pada industry kecil menengah melalui penerapan praktekpengolahan terbaik (GMP). Metoda yang digunakan dalam penelitian ini adalah analisa SWOT. Analisa SWOT merupakan salah satu alat analisis kualitatif yang digunakan untuk mengidentifikasi peluang dan ancaman dalam melakukan kegiatan dengan mengacu pada kekuatan dan kelemahan yang dimiliki stakeholders industri kecil menengah produk bakeri di kota Bogor. Penggunaan teknik Interpretive Structural Modeling (ISM) pada analisis SWOT untuk melihat hubungan kontekstual antar elemen dan hirarki untuk elemen penyusun strategi. Hasil analisis dari ke dua model (analisis SWOT dan ISM) dalam penelitian ini adalah strategi terbaik dengan keterbatasan ahli dalam rangka peningkatan mutu keamanan produk bakeri berdasarkan GMP.